Searches for lepton-flavour-violating decays of the Higgs boson in √s=13 TeV pp collisions with the ATLAS detector - Aad, Georges; Anders, Christoph; Andrei, George Victor; Antel, Claire; Bolz, Arthur; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Franchino, Silvia; Geisler, Manuel Patrice; Helary, Louis; Jongmanns, Jan; Klassen, Martin; et al. (Physics letters, 2020)
This Letter presents direct searches for lepton flavour violation in Higgs boson decays, H→eτ and H→μτ, performed with the ATLAS detector at the LHC. The searches are based on a data sample of proton-proton collisions at a centre-of-mass energy s=13 TeV, corresponding to an integrated luminosity of 36.1 fb−1. No significant excess is observed above the expected background from Standard Model processes. The observed (median expected) 95% confidence-level upper limits on the lepton-flavour-violating branching ratios are 0.47% (0.34−0.10+0.13%) and 0.28% (0.37−0.10+0.14%) for H→eτ and H→μτ, respectively.
Available online: 4 November 2019
Im Titel steht der Buchstabe "s" unter dem Wurzelsymbol
Gesehen am 25.02.2020
The ATLAS Collaboration: G. Aad, C.F. Anders, V. Andrei, C. Antel, A.E. Bolz, M. Dunford, D.E. Ferreira de Lima, S. Franchino, M.P. Geisler, L. Helary, J. Jongmanns, M. Klassen, M. Kolb, A. Krishnan, A. Kugel, M. Lisovyi, H. Meyer Zu Theenhausen, F. Napolitano, P.S. Ott, M. S̜ahinsoy, A. Schoening, H-C. Schultz-Coulon, T.M. Spieker, R. Stamen, P. Starovoitov, S. Suchek, L. Vigani, J. Wang, S.M. Weber, M. Wessels, X. Yue [und weitere]